Preventive Care Utilization among Adults with Hearing Loss in the United States - Fioravante, Nicholas; Deal, Jennifer A.; Willink, Amber; Myers, Clarice; Assi, Lama (Seminars in Hearing, 2021)
Hearing loss (HL) can negatively impact patient–provider communication and limit access to health promotion information, which may lead to decreased preventive care utilization. Using data from the 2015 and 2018 National Health Interview Survey, we examined the association between perceived HL with and without hearing aid use with self-reported age-appropriate uptake of breast and colon cancer screening, and influenza and pneumococcal vaccination. In models adjusted for sociodemographic characteristics, access to care, and health status, people with HL had lower odds of receiving breast cancer screening (odds ratio [OR] = 0.83, 95% confidence interval [CI] = 0.72–0.96) and higher odds of receiving pneumococcal vaccination (OR = 1.11, 95% CI = 1.00–1.24) relative to those without HL. There were no differences in their colon cancer or influenza vaccination uptake. Compared with those without HL, people with HL who used hearing aids had increased odds of colon cancer screening and influenza and pneumococcal vaccination, while people with HL who did not use hearing aids were less likely to report cancer screening. Overall, Americans with untreated HL were less likely to report completing cancer screening. Hearing aid use may modify the association between HL and preventive care uptake. Screening for HL in primary care settings and communication trainings for providers may help reduce cancer screening disparities.
Keywords: hearing loss; preventive care; hearing aids; patient–provider communication